Comparison of the Health Status of Uninsured Diabetic Patients Presenting for an Initial Visit to an Urban Free Clinic to Diabetic Patients from the National Health and Nutrition Examination Survey - Dalrymple, Nathan; Hidalgo, Michael; Desai, Anjali (Journal of Student-Run Clinics, 2020)
Background: We compare the health status of uninsured diabetic patients presenting for their initial visit at the Cooper Rowan Clinic (CRC) to insured and uninsured diabetic respondents of the National Health and Nutrition Examination Survey (NHANES). By establishing a baseline health status of CRC patients and comparing to NHANES respondents, we aim to identify how insurance status may be associated with health outcomes of this at-risk population. Methods: CRC patients with diabetes and insured and uninsured NHANES respondents with diabetes were compared based on health indicator goals established by the American Diabetes Association (ADA). Specifically, we used chi-squared tests to compare the proportion of individuals in each group that met ADA health indicator goals for hemoglobin A1c (HbA1c), blood pressure, low-density lipoprotein (LDL), and high-density lipoprotein (HDL). Then, we used post hoc one-way ANOVA to identify significant differences in the mean measurements of each of the health indicators. Results: CRC patients presenting at their initial visit have higher mean HbA1c than insured NHANES respondents (p<0.001) but similar mean HbA1c to uninsured NHANES respondents. CRC patients at their initial visit have higher blood pressures compared to insured and uninsured NHANES respondents (p<0.001). There were no significant differences in HDL and LDL between groups. Conclusions: This study adds to the literature describing the health status of uninsured diabetics. We show a positive association between insurance status and the control of HbA1c and blood pressure but no effect on HDL or LDL. CRC patients at their initial visit are less likely to be at blood pressure goal than both insured and uninsured NHANES respondents.